(untitled) (Ilm fan taraqqiyotida raqamli iqtisodiyot va zamonaviy ta’limning o’rni hamda rivojlanish omillari, 2025)
Abstract: This conference paper delves into the main determinants that influence the size and growth of the shadow economy. By examining economic, social, and institutional factors, this study aims to shed light on the underlying drivers of informal economic activities. Through a comparative analysis of international experiences, this research provides insights into common trends and challenges, offering valuable implications for policymakers and researchers.